The Capital Market Reaction To The Corona Covid-19 Virus Outbreak Events: Reaksi Pasar Modal Terhadap Peristiwa Wabah Virus Corona Covid-19 - Wardah Azizah; Nurasik (Academia Open, 2020)
This study aims to get a real picture of the Capital Market Reaction to the Corona Covid-19 Virus Outbreak (Study on LQ-45 Companies Listed on the Indonesia Stock Exchange). The analytical tool used is descriptive statistical analysis and classical assumption test. To test the hypothesis, it is done using data analysis in the form of Paired Sample T-Test using the statistical program "Product and Service Solution" (SPSS). The results of hypothesis testing using paired sample t-test obtained t-value with a significant value of 0.000 (0.000 <0.05). From these results, it can be stated that the hypothesis is accepted, which means that there is a significant difference in abnormal returns before and after the Corona / Covid-19 Virus Outbreak. The difference in Abnormal Return on the test results has a positive value, this shows that if the Corona / Covid-19 Virus Outbreak has increased, the Abnormal Return value will increase.